Fast‐acting bactericidal activity of olanexidine gluconate againstqacA/B‐positive methicillin‐resistantStaphylococcus aureus. Issue 6 (June 2019) - Nakaminami, Hidemasa; Takadama, Shunsuke; Okita, Miki; Sasaki, Mari; Noguchi, Norihisa
Abstract : N/A: The qacA/B gene is one of the major determinants of resistance to antiseptics in methicillin‐resistant Staphylococcus aureus (MRSA). Here, we compared the fast‐acting bactericidal activity of skin antiseptics, including olanexidine gluconate (OLG), a new biguanide antiseptic agent introduced in Japan, against clinical qacA/B ‐positive MRSA strains by determination of minimum bactericidal concentration and time‐kill assay. Our findings provide, for the first time, data indicating that the fast‐acting bactericidal activity of OLG against qacA/B ‐positive MRSA is higher than that of chlorhexidine gluconate, even though both are biguanide antiseptics.